Operacje w obszarze Europejskiej Polityki Bezpieczeństwa i Obrony – uwarunkowania i perspektywy rozwoju - Przybylska-Maszner, Beata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The analysis presented in this paper is based on a research assumption that the process of shaping of the Common Foreign and Security Policy, in particular its defense component, is affected by the dynamically changing influences (of the Member States) within the EU and the influence of the institutional mechanism of the EU and Member States. The shaping of this policy encounters numerous obstacles, the main one being the common political will of Member States, which is necessary for external operations related to the challenges to be met at the EU level.